Acehnese Women’s Move in Academic Leadership in 2020 - Basri, Basri; Sari, Rita; Nazar, Muhammad; Putra, Andhika Jaya (SCAD Independent, 2022)
This study discussed the role of Acehnese women in academic institutions within the public leadership structure over the past decade. Recruiting process, placement, and the fulfillment of women’s quotas in cross-sectoral at the institutions become a major concern due to a patriarchal model applied in Aceh. A survey of qualitative research was applied to find out the involvement of female lecturers at Islamic academic institutions in Aceh. The questionnaire was distributed to 58 respondents and 6 of them were selected to be interviewed. The data was analyzed by restatement, description, interpretation, and conclusion drawing. The result showed that approximately 50% of women worked as first-line managers, more than 35% were as middle-line managers, and 15% were as top managers. It was a milestone of sustainable development efforts over the past decade.